A Comparative Study on Swarm Intelligence Techniques for Charg ing Plug-in Hybrid electric Vehicles - RAHMAN, IMRAN (2016)
Green technologies gain popularity to reduce the pollution and gives higher pen etration of renewable energy source in the transportation. In the line of this research, which induce that the extensive involvement of plug-in hybrid electric vehicles (PHEVs) requires adequate charging allocation strategy using a combination of smart grid systems and smart charging infrastructures